Evaluation of the anaerobic biodegradability of household organic waste in the Kinshasa City - NSIMBA, Beaudrique Bodrigue; Luhata, Pierre L.; Mbuyi, Haddy K.; inkoto, clement; Basosila, Norbert L.; Mpiana, Pius Tshimankinda (Orapuh Journal, 2024)
IntroductionAnaerobic digestion (AD) can be used to produce a more environmentally friendly form of energy from municipal solid waste (MSW) and to clean up urban environments.  The application of this technology to MSW produced in Kinshasa city (KC) is highly desirable to alleviate the waste management problem it currently faces and to combat indoor air pollution caused using biomass energy, which causes over 1.1 million deaths in Africa every year. However, the successful implementation of AD technology in Kinshasa City (KC) will depend on the level of anaerobic biodegradability (AB) of its MSW.PurposeThis work aimed to assess the AB of household organic waste (HOW) produced in large quantities in the KC, namely: leaves and stems of Manihot utilissima (MU), leaves of Mangifera indica (MI), leaves of Persea americana (PA), stems of Amaranthus viridis (AV), stems of Ipomoea batatas (IP) and peels of Musa paradisiaca (MP).MethodsAB tests were carried out under mesophilic conditions in 750 mL bottles. These bottles were filled with a mixture consisting of 6.7 g, 13.3 g, or 50.0 g DW/L of these waste products (substrates); inoculum, at a substrate/inoculum ratio of 4:1 and water, at a substrate/water ratio of 1:4. After 70 days of AD, the methane yield (BMP) of each substrate was then calculated.ResultsThe highest BMP (0.09534 ± 0.00024 m3 CH4/kg.VS) was recorded for stems of AV at a concentration of 13.3 g DW/L, while leaves of PA at a concentration of 50.0 g DW/L gave the lowest BMP (0.00860 ± 0.00023 m3 CH4/kg.VS). Stems of AV stems and leaves of MU, and peels of MP showed good AB, compared with stems of IB and leaves of MI and PA. Co-digestion of these wastes is desirable to further improve their AB and enable the implementation of household-scale AD technology in KC.ConclusionThe results obtained confirm that this waste could be recycled by AD to produce a clean form of energy for cooking and to clean up the KC.